Ocular manifestations of canine transmissible venereal tumour: a retrospective study of 25 cases in Greece. (16th May 2015) - Komnenou, A. Th; Thomas, A. L. N.; Kyriazis, A. P.; Poutahidis, T.; Papazoglou, L. G.
Abstract : Transmissible venereal tumour (TVT) is a sexually transmitted neoplasm that frequently affects dogs of either sex, in tropical and subtropical regions. TVT primarily involves the external genitalia, although extragenital sites have also been reported. This study describes the ocular manifestations of TVT in 25 naturally infected dogs and their response to treatment. Seventeen male and eight female dogs were included in the study. TVT ocular lesions were either unilateral (21 dogs) or bilateral (four dogs). Ocular lesions as the single manifestation of TVT were seen in 22 animals. One dog presented external genitalia involvement while two others were found to have tumours in the oral and nasal mucosa. Variably sized multilobular tumour masses with irregular surface were noticed on the bulbar conjunctiva of the nictitating membrane in 17 dogs, on the conjunctiva of the upper eyelid in five dogs and on the conjunctiva of the lower eyelid and adjacent skin in three dogs. Deep ulcerative keratitis was observed in eight animals. TVT diagnosis was based on cytology and histopathology. The large eye masses were surgically excised. All dogs were treated with a single chemotherapeutic agent (vincristine). After four weeks of treatment, complete remission of the tumours was evident in all but one animal. Extragenital primary ophthalmic TVT can be completely eliminated by vincristine chemotherapy, while any further ocular damage is prevented with the combination of the above treatment and surgical excision.